The Relationship Between TLR 2 and 4 with Microbiota of Mouth and Nose in Hypersensitivity Type 1 Iraqi Patients - Aljubory, Sulafa A.; Alaubydi, Mouruj A. (Iraqi Journal of Science, 2019)
Hundreds of commensal bacteria are existed in the mouth and nose, and the interactions between these microbiotas and the Toll-like receptors (TLRs) in different parts of the upper respiratory tract, gastrointestinal tract, and immune cells maty assist to maintain the homeostasis of the immune system. Thus, it is importantto study the relationship between type one hypersensitivity and normal flora in the mouth and nose. Blood and saliva or sputum samples of seventy-one allergic patients were collected randomly in Baghdad/ Al- Zahraa center for asthma and allergies. Those patients were suffering from different types of hypersensitivity type1 such as skin and respiratory tract allergy (e.g, asthma and Rhinitis). The results revealed that the allergic females percentage were more than males. Staphylococcus spp., Lactobacillus and Fungi spp. isolated from the mouth and nose were more prevalent than other microorganisms among different age groups. In addition, most age groups were given significant variation in TLR2 level, while TLR4 recorded variation in female more than male patients.